Rekonstruksi Pemahaman Ayat 223 Al-Baqarah: Perspektif Zainab Al-Ghazali Terhadap Isu Kekerasan Seksual - Faizatut Daraini; Wildan Al Faizi; Muhaimin Zen; Ade Naelul Huda (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2025)
This article aims to examine the phenomenon of sexual violence that is currently prevalent in society, with a focus on the interpretation of Quranic verses related to this issue. The research employs a qualitative approach through a literature review, aiming to understand the meaning of sexual violence in the Quran and identify the factors influencing it. The findings indicate that one of the main factors contributing to sexual violence is the imbalance in power relations, superiority, and gender inequality. Zainab Al-Ghazali's interpretation of QS. Al-Baqarah 223 reveals the view that women are highly valuable and noble, likened to a field where life grows (maudi'ul walad). Based on these findings, the study recommends the need for a gender justice-based approach in understanding Quranic verses to support the prevention of sexual violence and raise awareness of the importance of respecting women's rights in society.